Antimicrobial and Membrane Stabilization Activity of Plant Extracts Against Pathogenic Bacteria and Fungi - Tumpa, Nadia Islam; Rahman, Md Shafiqur; Manchur, Mohammed Abul (Bangladesh Journal of Microbiology, 2024)
The use and search for antimicrobial drugs derived from plants have accelerated in recent years. The present study was aimed to determine the antimicrobial, antibiofilm and membrane stabilization activities of plant extracts. Crude extracts of four plants namely, Mikania scandens (L.), Mimosa pudica (L.), Murraya paniculata (L.), and Syzygium aromaticum (L.) were tested against eleven human pathogens including four biofilm producing bacterial strains Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Staphylococcus aureus, and one fungal strain Candida albicans. The antimicrobial activities as well as minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts were evaluated using disc diffusion and macro-broth dilution methods respectively. Among the plant extracts, ethanol extract of S. aromaticum exhibited the largest zone of inhibition 35 mm in diameter against Bacillus subtilis at 500 µg/disc concentrations. The lowest MIC (1000 µg/ml) and MBC (2500 µg/ml) were determined against P. aeruginosa with the same extract of S. aromaticum. In case of time kill assay, S. aromaticum extract showed the lowest optical density (OD600) 0.2 against E coli in 3h at MBC concentration. Moreover, the same extract of S. aromaticum displayed the strong antibiofilm activity, inhibiting 100% biofilm formation of E. coli at 2×MIC concentration. Furthermore, in vitro experiment was performed to evaluate membrane stabilization activity of plant extracts and S. aromaticum showed 100% activity in stabilizing cell membranes, preventing hemolysis of red blood cells. Therefore, this study provides valuable insight for designing antimicrobial products to efficiently eliminating human infections, and the plant extracts could be the potential antimicrobial agent. Bangladesh J Microbiol, Volume 40, Number 2, December 2023, pp 76-85